Building Integrity From Within: The Role Of Organizational Culture And Commitment In Preventing Fraud In Student Organizations At Universitas Islam Bandung - Nashrullah, Hasan; Maemunah, Mey; Purnamasari, Pupung (Journal of Economics and Business UBS, 2025)
This study aims to analyze the role of organizational culture and organizational commitment in preventing fraud in student organizations at Bandung Islamic University. Fraud, which is generally associated with profit-oriented entities, can also occur in non-profit organizations such as student organizations, thereby threatening the integrity and sustainability of the organization. This study uses a verifiable method with a quantitative approach. Data were collected through a survey of 121 student organization administrators from various student organizations. Statistical analysis was performed to test the hypothesis regarding the influence of organizational culture and organizational commitment on fraud prevention. The results show that organizational culture and organizational commitment have a positive and significant effect on fraud prevention. An organizational culture that emphasizes teamwork, results orientation, and human orientation encourages ethical behavior and reduces fraudulent practices. Meanwhile, organizational commitment, which consists of affective, continuance, and normative commitment, encourages loyalty, responsibility, and compliance with organizational values, thereby strengthening fraud prevention efforts. These findings emphasize the importance of building an ethical culture and strengthening member commitment as a strategy for improving governance and transparency in student organizations.